Can the microbiota predict response to systemic cancer therapy, surgical outcomes, and survival? The answer is in the gut. Issue 4 (2nd April 2020) - El Bairi, Khalid; Jabi, Rachid; Trapani, Dario; Boutallaka, Hanae; Ouled Amar Bencheikh, Bouchra; Bouziane, Mohammed; Amrani, Mariam; Afqir, Said; Maleb, Adil
ABSTRACT: Introduction: The gut microbiota seems to play a key role in tumorigenesis, across various hallmarks of cancer. Recent evidence suggests its potential use as a biomarker predicting drug response and adding prognostic information, generally in the context of immuno-oncology. Areas covered: In this review, we focus on the modulating effects of gut microbiota dysbiosis on various anticancer molecules used in practice, including cytotoxic and immune-modulating agents, primarily immune-checkpoint inhibitors (ICI). Pubmed/Medline-based literature search was conducted to find potential original studies that discuss gut microbiota as a prognostic and predictive biomarker for cancer therapy. We also looked at the US ClinicalTrials.gov website to find additional studies particularly ongoing human clinical trials. Expert commentary: Sequencing of stool-derived materials and tissue samples from cancer patients and animal models has shown a significant enrichment of various bacteria such as Fusobacterium nucleatum and Bacteroides fragilis were associated with resistant disease and poorer outcomes. Gut microbiota was also found to be associated with surgical outcomes and seems to play a significant role in anastomotic leak (ATL) after surgery mainly by collagen breakdown. However, this research field is just at the beginning and the current findings are not yet ready to change clinical practice.